Multivariate analysis for coronary heart disease in heterozygote familial hypercholesterolemia patients. (31st January 2018) - Sánchez Muñoz-Torrero, Juan Francisco; Rivas, Maria D; Zamorano, Jose; Joya-Vázquez, Pedro Pablo; de Isla, Leopoldo Perez; Padro, Teresa; Mata, Pedro; the SAFEHEART Investigators,
Aim: rs599839 polymorphism has been related with low levels of cholesterol and reduced coronary heart disease (CHD).Methods: We investigated the frequency of this polymorphism in patients with heterozygous familial hypercholesterolemia (HeFH) in the Spanish familial hypercholesterolemia cohort, 230 with and 202 without CHD. Results & discussion:  A lower G-allele prevalence was observed in HeFH patients with CHD with respect to controls, 35 versus 45%, respectively (p = 0.029), suggesting a protective effect. However, it was found that there was no association between rs599839 alleles and CHD in the multivariate analysis.Conclusion: The frequency of the protective G-allele of the rs599839 polymorphism was lower in HeFH patients with CHD compared with those HeFH patients without CHD. However, its role in HeFH may be masked by very high levels of cholesterol.